Pengaruh Keselamatan Kerja, Kesehatan Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Sinar Sosro Kantor Penjualan (KP) Jember - Nur Sabilillah Ayuningtias; Toni Herlambang; Tatit Diansari Reskiputri (Universitas Muhammadiyah Gresik, 2021)
Background - The company has provided occupational safety and health facilities to avoid work accidents, but employees still do not use the equipment that has been provided. This can affect the performance of employees in carrying out their work. Objective - This study aims to determine the partial effect of work safety (X1), occupational health (X2) and work environment (X3) towards employee performance (Y) of PT Sinar Sosro KP Jember. Design/Methodology/Approach - This research used a quantitative method approach. The population in this study were the employees of PT Sinar Sosro KP Jember and covered 32 employees as the number of samples. The data collection technique used was a questionnaire with data instrument tests (validity and reliability tests), classical assumption tests (multicollinearity test, normality test, and heteroscedasticity test), multiple linear analysis and hypothesis testing (t test and coefficient of determination) with the help of SPSS 21.0 for Windows software application. Findings - The results of this study indicate that, partially, the work safety variable (X1) has a significant effect on employee performance (Y) with significance value of 0.026. Partially, the occupational health variable (X2) has a significant effect on employee performance (Y) with significance value of 0.028. While the work environment variable (X3) partially has a significant effect on Employee Performance (Y) with significance value of 0.013. The adjusted R-squared value of 0.799. This indicates that 79% of variations in employee performance variable can be well explained by occupational safety, occupational health and work environment variables. The remaining value of 0.21 or 21% is influenced by other variables that are not examined in this study. Research implications - The results of this study are expected to be input and as additional information for the company in providing occupational safety and health facilities to the performance of employees at PT Sinar Sosro KP Jember. Research limitations - The limitations of this study are that it only uses three variables while there are many other factors that can affect employee performance, and the sample used is still small so it cannot be generalized to all companies.